Parser evaluation using textual entailments - Eker, Önder. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2009., 2009)
Syntactic parsing is a basic problem in natural language processing. It can be de ned as assigning a structure to a sentence. Two prevalent approaches to parsing are phrase-structure parsing and dependency parsing. A related problem is parser evaluation. This thesis proposes Parser Evaluation using Textual Entailments as a dependency-based evaluation where a parse is represented as a list of simple sentences, similar to the Recognizing Textual Entailments task. Each entailment focuses on one relation. A priori training of annotators is not required. A program generates entailments from a dependency parse. Phrase-structure parses are converted to dependency parses to generate entailments. Additional entailments are generated for phrase-structure coordinations. Experiments are carried out with a function-tagger. Parsers are evaluated on the set of entailments generated from the Penn Treebank WSJ and Brown test sections. A phrase-structure parser obtained the highest score.
Keywords: Parsing (Computer grammar); Natural language processing (Computer science)